Composition and trophic structure of motile fauna populations in macrophytes of a natural CO2 vent system - ANDOLINA, CRISTINA; Martínez Crego B.; Vizzini S.; Massa Gallucci A.; Gambi M. C. (XXIV Congresso della Società Italiana di Ecologia, 2014)
As a consequence of global change, ocean acidification is predicted to increase progressively in the next centuries and evidence suggests that decreased levels of pH could lead to severe modifications in marine communities. Levante Bay in Vulcano Island (Aeolian Archipelago, Italy) hosts a shallow submarine volcanic CO2 vent, representing a natural laboratory suitable to study the effects of ocean acidification on marine ecosystems. However, in addition to direct CO2 effects, volcanic emissions may also increase a number of trace elements, providing harsh features to the surrounding environment. The aim of this work was to examine the motile fauna populations associated to macrophytes, Cymodocea nodosa and macroalgal beds, in order to detect any change in composition and trophic structure attributable to the peculiar features of the volcanic vent. We compared the structure of populations sampled in a site close to the vents (weakly acidified) and in a control site (normal pH conditions). Samples were collected in May 2013 using an airlift sampler on 30 cm quadrats. Results revealed clear differences in macrophyte composition, cover and biomass between the two sites, as well as in the structure of the faunal community, with the weakly acidified site showing higher abundances of polychaetes and amphipods and a marked reduction in molluscs in comparison with the control site. Furthermore, stable isotope analysis showed that in the weakly acidified site δ13C and δ15N signatures of primary producers were depleted, while the isotopic niche space of the motile fauna became narrower and markedly shifted towards lower values. These findings highlight the importance of studying the effects of ocean acidification on the composition and structure of food webs within benthic communities and its ecological implications are discussed in terms of diversity and local adaptation.